Modified perceptual training in sport: A new classification framework - Hadlow, S. M.; Panchuk, D.; Mann, D. L.; Portus, M. R.; Abernethy, B. (Journal of Science and Medicine in Sport, 2018)
Objectives: To overview a framework that provides a theoretically-grounded approach to predicting the types of modified perceptual training tasks that will stimulate transfer of improved perceptual skills to sport performance environments. Modified perceptual training (MPT) collectively describes on- or off-field sports training tasks that are specifically designed to develop visual and perceptual-cognitive skill. Traditional training approaches in sport include sports vision training and perceptual-cognitive training, while recently, new technologies have enabled a broad range of additional MPT tools to become available to coaches and athletes. Design: Short literature review and opinion article. Methods: Literature in the fields of sports vision training and perceptual-cognitive training are summarised and contrasted. A selection of emerging MPT technologies are then overviewed. This leads to the identification of three interacting factors of MPT task design that may influence the task`s capacity to transfer improved training performance to actual competition: (i) the targeted perceptual function, (ii) stimulus correspondence, and (iii) response correspondence, which are assimilated with key tenets of representative learning design. Results: These three theoretically-grounded differences are adopted to support and justify the structure of the Modified Perceptual Training Framework which sets out predictions for future research to test in order to clarify the transfer effect of MPT tools. Conclusions: The application of the Modified Perceptual Training Framework may assist in future testing, design and selection of beneficial training tools in sport and as such, is predicted to have significant impact in empirical and practical settings.